If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (3x + -1)(4x + -3) = 0 Reorder the terms: (-1 + 3x)(4x + -3) = 0 Reorder the terms: (-1 + 3x)(-3 + 4x) = 0 Multiply (-1 + 3x) * (-3 + 4x) (-1(-3 + 4x) + 3x * (-3 + 4x)) = 0 ((-3 * -1 + 4x * -1) + 3x * (-3 + 4x)) = 0 ((3 + -4x) + 3x * (-3 + 4x)) = 0 (3 + -4x + (-3 * 3x + 4x * 3x)) = 0 (3 + -4x + (-9x + 12x2)) = 0 Combine like terms: -4x + -9x = -13x (3 + -13x + 12x2) = 0 Solving 3 + -13x + 12x2 = 0 Solving for variable 'x'. Factor a trinomial. (1 + -3x)(3 + -4x) = 0Subproblem 1
Set the factor '(1 + -3x)' equal to zero and attempt to solve: Simplifying 1 + -3x = 0 Solving 1 + -3x = 0 Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -3x = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -3x = 0 + -1 -3x = 0 + -1 Combine like terms: 0 + -1 = -1 -3x = -1 Divide each side by '-3'. x = 0.3333333333 Simplifying x = 0.3333333333Subproblem 2
Set the factor '(3 + -4x)' equal to zero and attempt to solve: Simplifying 3 + -4x = 0 Solving 3 + -4x = 0 Move all terms containing x to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + -4x = 0 + -3 Combine like terms: 3 + -3 = 0 0 + -4x = 0 + -3 -4x = 0 + -3 Combine like terms: 0 + -3 = -3 -4x = -3 Divide each side by '-4'. x = 0.75 Simplifying x = 0.75Solution
x = {0.3333333333, 0.75}
| x+7=x-2 | | 3x=6y-9 | | 5q=-25 | | 3x-(2x+5)=0 | | -4(1+r)=32 | | 2*6=12x | | -4(-2+x)=-16 | | -4(-2+x)=-6 | | -77=-7x | | 180-x=14*x | | 8x^2+21x-12=0 | | F(3)-9=5n+4n | | 180-x=19*x | | -7=a-6 | | 3+3(x+6)-45+6-8/2+3=27 | | 3+3(x+6)-4*5+6-8/2+3=27 | | 50+7x-8x+3x=-10 | | -19=v-15 | | 180-x=19(90-x) | | 26-4x+12+6x=-16 | | 180-x=14(90-x) | | 40+2x-3x+5x=40 | | 40x+2x-3x+5x=40 | | -5(4b+4)+(21b-3)=0 | | (13b-9)-3(4b+4)=-5 | | 5+2*5= | | -3x+15=-10+10 | | 45-9x=5x-25 | | 5+2*-5= | | 3*-5=5+2*-5 | | 3b+-1=5 | | 9x-6x=27 |